Saccharomyces cerevisiae surface display of endolysin LysKB317 for control of bacterial contamination in corn ethanol fermentations - Lu, Shao-Yeh; Liu, Siqing; Patel, Maulik H.; Glenzinski, Kristina M.; Skory, Christopher D. (Frontiers in Bioengineering and Biotechnology, 2023)
Control of bacterial contamination in bioethanol fermentation facilities has traditionally relied on chemical-based products such as hop acids and the use of antibiotics. Recent emphasis on antibiotic stewardship has prompted new research into development of alternative approaches to microbial remediation strategies. We recently described a recombinant peptidoglycan hydrolase, endolysin LysKB317, that inhibited Lactobacillus strains in corn mash fermentation. Here, Saccharomyces cerevisiae EBY100 was used to anchor recombinant LysKB317 using cell surface display with the a-agglutinin proteins Aga1p-Aga2p. Immunostaining and confocal fluorescence were used for localization of the extracellular interface of the cells. Yeast surface expressed endolysin demonstrated an 83.8% decrease in bacterial cell counts compared to 9.5% decrease in control yeast. Recombinant S. cerevisiae expressing LysKB317 used for small-scale corn mash fermentation, when infected with Limosilactobacillus fermentum, showed the ability to proactively control bacterial infection for 72 hours with at least 1-log fold reduction. HPLC analysis of fermentation products showed improved ethanol concentration from 3.4 % to at least 5.9 % compared to infection-only control and reduced levels of lactic and acetic acid from 34.7 mM to 13.8 mM and 25.5 mM to 18.1 mM in that order. In an optimized yeast surface display system, proactive treatment of bacterial contaminants by endolysin LysKB317 can improve fermentation efficiency in the presence of L. fermentum contamination.